Conservation of Manilkara salzmannii in an Atlantic Forest fragment through the study of fruits and seeds - Freire, Ageu da Silva Monteiro; Chagas, Kyvia Pontes Teixeira das; Medeiros, Anna Luiza Araújo; Santos, Jéssica Ritchele Moura dos; Vieira, Fábio de Almeida (Iheringia, Série Botânica., 2024)
The objective of the study was to evaluate the biometry of fruits and seeds and the emergence of seedlings on different substrates of Manilkara salzmannii (A. DC.) H. J. Lam (massaranduba). We measured 100 fruits and 116 seeds and recorded biometric variables to calculate descriptive statistics, and applied correlation analysis. For seedling emergence, we evaluated four substrate treatments (T1: bovine manure + sand in 2:1 proportion; T2: bovine manure + sand in 1:1 proportion; T3: sand; and T4: sand + clay in 1:1 proportion). The fruits had average length of 16.67 mm, width of 17.10 mm and fresh mass of 3.20 g. The seeds had average length of 10.65 mm, width of 7.13 mm, thickness of 4.68 mm, and fresh mass of 0.22 g. There was a positive correlation between the fruit and seed variables. The lowest seedling emergence percentage was produced with 1:1 sand/clay ratio, which in contrast provided the highest emergence speed index (ESI). The biometric characteristics of fruits and seeds and the identification of the best substrate for seedling emergence will serve as a basis for seedling production and improve understanding of the species’ propagation.